Identifikasi Pola Sebaran Titik Api (Hotspot) dan Penyebab Kepadatannya di Sekitar Kawasan Taman Wisata Alam (TWA) Camplong (Studi Kasus di Desa Oebola Dalam Dan Desa Sillu, Kecamatan Fatuleu, Kabupaten Kupang) - Petra A. J. Benu; Ludji Michael Riwu Kaho; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Each forest area has different causes of fire. The source of the fire needs to be known in order to plan and determine appropriate control efforts so that forest fires do not spread or can be overcome. This research uses a qualitative approach that seeks to examine and describe the factors that cause forest fires and efforts to control forest fires in Camplong Nature Park. The data collection method uses purposive sampling technique. The results showed that indications of forest and land fires can be predicted through satellite image interpretation for a pixel that has a threshold temperature in a place. The number of annual hotspots during 2017 - 2021 was 333 points with Sillu Village having 282 hotspots or 84% of the total and Oebola Village having 51 points or 15% of the total. The highest occurrence of hotspots is in four types of land cover, namely agricultural land cover with 135 hotspots (40.54%), forest land cover with 85 hotspots (25.53%), savanna land cover with 59 hotspots (17.72%), shrub land cover with 42 hotspots (12.61%). Relatively fewer hotspots were found in the settlement land cover type with 8 hotspots (2.40%), rice field land cover with 3 hotspots (0.90%), and the lowest in the river area with 1 hotspot (0.30%). The highest number of hotspots based on the function of the forest area was in the Other Use Area (APL) with 168 hotspots (50.45%), Protection function (HL) with 116 hotspots (34.83%), Production function (HP) with 42 hotspots (12.61%) and the lowest in the Conservation area with 7 hotspots (2.10%).